Employee Stock Option: Realization, Taxation and Prospects in Lithuania - Tamulionytė, Luka; Tamašauskas, Nedas (Vilnius University Open Series, 2024)
This yearly paper analyzes the implementation, taxation and prospects of employee stock options, examining the existing legal framework and practical examples of implementation. Among other things, the concept of employee stock option is explained, the problems arising due to the non-enforcement of the concept in legal acts are reviewed as well. It also examines the perception of this institute from the point of view of civil and tax law, which affects the correct realization of the stock option in practice. The work analyzes the changes to the laws adopted by the legislator, which determine the changes and peculiarities of the realization and taxation of stock options: the liberalization of the preferred stock institute and the establishment of personal income tax benefits granted in compliance with the established conditions. An analysis of these legislative changes provides an overview of the attractiveness of employee stock options and the emerging issues that employers and employees will face. The yearly paper, among other things, briefly reviews the perspectives of employee stock options in Lithuania.
Keywords: -